Kajian Terhadap Desain Permainan Basket untuk Siswa Fase C di Kecamatan Paguyaman Boalemo - Zenius Tobuhu; Hariadi Said; Mirdayani Pauweni (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The values inherent in basketball—such as teamwork, responsibility, sportsmanship, and discipline—can help develop students' character from an early age, making the sport a foundational component of physical education (PJOK) learning in elementary schools. However, this basketball learning is often hindered by a lack of facilities and equipment. Therefore, the purpose of this paper is to review the literature and produce a preliminary design draft for a basketball game deemed suitable for students in Phase C in Paguyaman Boalemo District. The qualitative descriptive approach in this paper involves four stages: data collection, data reduction, data display, and conclusion drawing/verification. The study produced a draft design for the “Lilingo” basketball that outlines its definition, facilities and equipment, and playing techniques. This initial draft can be taken to the next stage in research and development, namely the expert validation stage. Keywords: Basketball Lilingo, Design, Phase C, Game, Elementary School Students